ANALISIS PENGARUH CAR, NPL, LDR, DAN BOPO TERHADAP PROFITABILITAS (ROE) PADA BANK UMUM SYARIAH (Studi Kasus Pada Bank Umum Syariah di BEI 2008 – 2012) - Rida Hermina; Edy Suprianto (Jurnal Akuntansi Indonesia, 2014)
The banking sector is one of the important sectors in the Indonesian economy , because banking is one of the depository financial institution that espouses the main function to raise funds from the public and mobilize communities by channeling funds back to the community in the form of utilization of funds or investment activities. Advantages of banking can be influenced by many factors, including the presence and absence of lending capita, while some factors that inhibit banking profit is the presence of bad loans and poor management performance.From the background is exactly the author tries to analyze the effect of CAR, NPL, LDR, and BOPO to profitability (ROE) in Islamic banks, because the existence of Islamic banking in Indonesia is increasing. The current study was conducted quantitative kind, it is there is a causal relationship, to test the profitability ( ROE ) as a measure of thedependent variable with the independent variables are CAR, NPL, LDR, and BOPO. There are 6 samples contained Islamic banks are routinely reported on the Stock Exchange ‘s financial statements for 5 consecutive years since 2008 to 2012 it is Bank Muamalat , Bank Syariah Mandiri, Bank BNI Syariah, Bank Mega Syariah, Bank BRI Syariah and Bank Syariah Bukopin. The test with SPSS, the normality test analysis technique, the classical assumption test , multiple linear regression, partial test ( t test ), and test the coefficient of determination (adjusted R2 ). This study shows that the results of the independent factors affecting the profitability ( ROE ) is the ratio of BOPO, which is the level of performance due to the existence of his company management BOPO considered capable and efficient inincreasing bank profits. While the CAR (capital), LDR (loan), and NPL (non-performing loans) has no effect because the ratio of the numbers of the three smaller proven and covered by another larger factor .